The study of some significant features of the non pleasant lips in adult girls (Study on the frontal photos) - Hasan, Abdulkarim (Latakia University Journal -Medical Sciences Series, 2018)
The improvement of the Facial aesthetic of the soft tissues is a very important aim of the orthodontic treatment, so ît is necessary to find a standard morphological criteria for this subjects specially the lips which affect on the aesthetic features. The aim of this study is to determine some significant features of the non pleasant lips in adult girls using frontal photos. The sample of this study consists of 30 frontal photos for adult girls with non pleasant lips according to the evaluation of special committee. The photos were studied and the data were analyzed by anova and person analyses therein the study showed different relationships between the studied variables and the degree of the facial beauty where the thickness of the lips had the greatest role in evaluation according to the statistical study . The result may be affected by the opinion of the society which consider the full lips as an aesthetic guide for girls. دراسة بعض الصفات الشكلية المميزة للشفاه غير الجذابة لدى الإناث من البالغين (دراسة على الصور الضوئية الجبهية) يشكل تحسين المظهر الجمالي للنسج الرخوة الوجهية هدفاً هاماً من أهداف المعالجة التقويمية من هنا كان لابد لنا من إيجاد معايير فاصلة وصفات شكلية مميزة لهذه العناصر وخاصة الشفاه لما لها من دور هام بإضفاء صفة جمالية على الشخص. يهدف هذا البحث لتحديد يعض الصفات الشكلية المميزة للشفاه غير الجذابة باستخدام الصور الضوئية الجبهية لدى الإناث من البالغين . تألفت عينة البحث من صور ضوئية جبهية ل ـ30 شابةً بعمر يتراوح بين 18- 25 عاماً على اعتبارهن من ذوي الشفاه غير الجذابة بعد تقييمهم من قبل لجنة خاصة. درست الصور الضوئية وتم تحليل البيانات باستخدام اختبار تحليل التباين Anova,و اختبار معامل الارتباط بيرسون حيث أظهرت الدراسة وجود علاقات مختلفة بين متغيرات الشفاه المدروسة ودرجة الجمال وكان لثخن الشفة العلوية التأثير الأكير تبعا للدراسة الإحصائية وغالباً أتت هذه النتيجة نتيجة تاثير ونظرة المجتمع على أفراده حيث يروج للشفاه الممتلئة على أنها مؤشر جمالي هام للإناث.